1979
DOI: 10.1086/337053
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ethephon on Cattleya aurantiaca (Orchidaceae) Seedlings

Abstract: In Callleya attrantiaca seedlings, ethephon _(2-chloroethylphosphonic acid, also known as Ethrel), slightly :icc~l~rated leaf development at c~ncentratlons between 2.5 and 20 ppm but suppressed it at 50 ppm. It inh1b1t~d leaf l~ng~h. at concentrations .of 2.5\ 5, and SO ppm but enh:inced it at 10 and 20 ppm. Root formation was mh1b1ted by concentrations higher than 2.5 ppm. Chlorophyll content of seedlings was highest on a medium containing S ppm ethephon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Since then, in vitro seed germination protocols have been established for many orchid species, and a number of media and salts have been used for germination and propagation ( Arditti and Ernst 1993 ). Orchid seeds and seedlings have often been reported not to require exogenous auxin ( Tamanaha et al . 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…Since then, in vitro seed germination protocols have been established for many orchid species, and a number of media and salts have been used for germination and propagation ( Arditti and Ernst 1993 ). Orchid seeds and seedlings have often been reported not to require exogenous auxin ( Tamanaha et al . 1979 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Cattleya seedlings, ethephon slightly increased leaf development at concentrations between 2 .5 and 20 mg 1 -' , but at 50 mg 1 -' it was toxic to seedlings [83] . In another study, it was shown for several orchid species that germination was not affected adversely, but leaf length and number were reduced significantly by ethephon at 10-50 mg l -' [25] .…”
Section: Seed Germination and Seedling Growthmentioning
confidence: 92%
“…The effects of ORC , DOR , DMS , LOR, BAT, and the controls were evaluated by the growth index (SPOERL 1948) method, which measures seedling development (three determinations per concentration); leaf length measurements (TAMANAHA et al 1979), using 100 seedlings per culture; and assays of chlorophyll content of entire seedlings (MACKINNEY 1941 ;AR-NON 1949 Chlorophyll content (a, b, total) of seedlings on ORC was equal to or higher than on the two controls except that, on 0.078 x 10-4 Mand 0.313 x 10-4 M, the total level was lower than on E ( fig. 3).…”
Section: Introductionmentioning
confidence: 99%
“…3)-and growth index ( fig. 1) , have proved useful in measuring orchid seed germination and seedling development (HARRISON 1973;ARDITII 1979;TAMANAHA et al 1979).…”
Section: Introductionmentioning
confidence: 99%